Documents on and from the history of economic thought and methodology - Johnson, Marianne F. (Marianne Frances); Johnson, Kirk.; Samuels, Warren J., 1933- (Bingley, U.K. : Emerald, 2008)
Volume 26C contains five sets of lectures taken by Glenn Johnson as a doctoral student in economics at the University of Chicago during 1946-7.Johnson went on to become a leading professor of agricultural economics at Michigan State University. At Chicago his professors were among the foremost in the country.They included Frank Knight, Milton Friedman, D. Gale Johnson, John U. Nef, and T. W. Schultz, several future Nobel Prize winners.Also included are notes by Mark Ladenson (also from Michigan State) at Northwestern and from a faculty seminar at MSU on comparative method.
Glenn Johnsons notes from Frank H. Knight's course in the history of economic thought, Economics 302, University of Chicago, winter 1947 / Glenn Johnson -- Glenn Johnson's notes from D. Gale Johnson's course on income and welfare, Economics 356, University of Chicago, spring 1947 / Glenn Johnson -- Glenn Johnson's notes from John U. Nef's course, Introduction to English economic history, University of Chicago, spring 1947 / Glenn Johnson -- Glenn Johnson's notes from Theodore W. Schultz's course on resource administration and policy, Economics 355, University of Chicago, fall 1946 / Glenn Johnson -- Mark Ladenson's notes from Frank W. Fetter's course on the history of economic theory, Economics D-18, Northwestern University, spring 1967 / Mark Ladenson -- Notes on a faculty seminar series on comparative method, by Stanley C. Ratner, Michigan State University, spring term, 1969 -- Glenn Johnsons notes from Milton Friedman's course in economic theory, Economics 300A, University of Chicago, winter quarter 1947 / Glenn Johnson.
Print version record
Keywords: Business & Economics -- General; Economic theory & philosophy; Economic history; Economics -- Study and teaching (Higher); Economics -- Methodology; Economics -- Research